Prevalence of hypogonadism in transfusion-dependent β-thalassemia patients of Bangladesh: investigating the role of serum ferritin level as a diagnostic tool - Romana Chowdhury; Mohammad Azmain Iktidar; Mushfiq Newaz Ahmed; Mohammad Mehedi Hasan; Md. Mazharul Hoque Tapan; Sheikh Saiful Islam Shaheen; Atiar Rahman; Ayesha Khatun (Hematology, Transfusion and Cell Therapy, 2023)
Introduction: Hypogonadism is one of the most frequent complications in transfusion-dependent thalassemia patients and early recognition and treatment is the core element in restoring impaired gonadal function. Despite the high burden of disease, relevant studies are scarcely addressing the gonadal function of such patients in Bangladesh. The pattern of gonadal function in transfusion-dependent thalassemia patients must be characterized before planning a generalized management plan. Moreover, since iron overload is a key reason behind hypogonadism in thalassemia patients, investigating the role of serum ferritin level as a diagnostic tool for hypongadism was also an aim of this study. Methods: This cross-sectional study was conducted at the Department of Transfusion Medicine of the Bangabandhu Sheikh Mujib Medical University. According to the inclusion and exclusion criteria, a total of 94 patients were enrolled in this study. A detailed history and thorough clinical examination were carried out in each patient and recorded using a pretested structured questionnaire. In addition, the laboratory assessment of serum ferritin, luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone and estradiol in serum were also performed. The data were analyzed using the STATA (v.16). Results: The mean age of the patients with transfusion-dependent thalassemia was 18.81 ± 4.65 (SD), with 53.3% of the patients being male. The overall prevalence of hypogonadism was 35.11%, 18.1% being normogonadotropic, 11.7% being hypogonadotropic and 5.3% being hypergonadotropic. The serum ferritin level was significantly higher (p < 0.001) in patients with hypogonadism (Eugonadal: 2,174.79 (± 749.12) ng/ml; Hypogonadal: 3,572.59 (± 1,199.49) ng/ml). The area under the receiver operating characteristic (ROC) curve of serum ferritin was high (0.83) and the p-value was highly significant (< 0.001). Conclusion: Therefore, the serum ferritin level and gonadal hormone analysis of transfusion-dependent thalassemia patients can be considered a screening tool for assessing gonadal function and early detection and prevention of hypogonadism.